Valuing the contribution of sport volunteering to subjective wellbeing: evidence from eight European countries - Kokolakakis, Themistocles; Schoemaker, Jelle; Lera-Lopez, Fernando; de Boer, Willem; Čingienė, Vilma; Papić, Alma; Ahlert, Gerd (Frontiers in Sports and Active Living, 2024)
Volunteering is a prominent and integral aspect of the activities undertaken by sports clubs in Europe. However, even with its growing importance, quantifying the monetary worth of this nonmarket activity, in terms of wellbeing, can present certain difficulties. Traditional approaches to valuing volunteering (i.e., replacement and opportunity cost approaches) do not fully capture the value of volunteering to individuals, as they do not consider the intangible benefits that individuals may derive from their participation.This research provides added value to the monetisation of volunteering in sport by applying the wellbeing valuation approach (WVA) for the first time to a cross-sectional data in eight European countries. A double instrumental variable approach was developed to correct for unobservable variables that may influence income and subjective wellbeing (SWB), and volunteering and SWB. This allows to estimate the causal impact of volunteering and income on SWB more accurately and assign a reasonable monetary value to this non-market activity.The results, based on a sample size of 1,091, show an income compensation for a volunteer, devoting on average 8.7 hours during a four-week period of €16 to €50 per hour, equivalent to between € 1,700 and € 5,200 per year, depending on the nationality of the volunteer. With these estimations insights into the value of volunteering in sports are provided, contributing to a better understanding of how this activity can be valued and supported. By recogniszing and accurately valuing the contributions of volunteers, sport organizations and policymakers can develop more effective strategies for promoting and supporting volunteering in sports.